Probable Creutzfeldt-Jakob Disease Presenting Dementia and Urinary Retention - Aiba, Yosuke (Case Rep Neurol, 2020)
We describe the case of an 80-year-old woman with probable Creutzfeldt-Jakob disease (CJD) presenting dementia and urinary retention. Although the number of patients previously examined, including ours, is small for conclusion, provided that other etiologies of urinary retention are carefully excluded, urinary retention seems to become a feature in CJD, presumably reflecting spinal cord pathology in CJD. Physicians are advised to evaluate pelvic floor function in CJD particularly by checking post-void residuals.